2001
DOI: 10.1111/1467-8535.00228
|View full text |Cite
|
Sign up to set email alerts
|

Design implications from a usability study of GramStain‐TutorTM

Abstract: To examine interface issues in an educational software program, we recruited twenty-two users in health sciences departments for a usability study. Using the GramStain-Tutor TM (GST) CD-ROM, these users performed tasks in navigating the program and using various interactive features. Their actions and comments were recorded with a digital video recorder and an audio recorder. The main results of our study are: (a) the majority of the users did not use the multiple navigational options available in the program;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Perceptions of ease of use included the unanimously positive comments regarding the constant navigation bar, which appears on the left side of all screens on the Web site. This result is consistent with the findings in other usability studies that users prefer a constant navigational indicator on all pages of a Web site (Kim et al, 2001).…”
Section: Qualitative Responsessupporting
confidence: 93%
See 3 more Smart Citations
“…Perceptions of ease of use included the unanimously positive comments regarding the constant navigation bar, which appears on the left side of all screens on the Web site. This result is consistent with the findings in other usability studies that users prefer a constant navigational indicator on all pages of a Web site (Kim et al, 2001).…”
Section: Qualitative Responsessupporting
confidence: 93%
“…The usability study by Kim et al (2001) similarly found that "subtle visual cues are likely to go undetected when an interface demands that a user recognize embedded text [and] navigational features" (p. 603). These researchers recommend enlarging or otherwise enhancing the visibility of text, through distinct and consistent colors for certain types of navigation or content themes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This recommendation is supported by previous work, which has spotlighted the fact that few evaluations of the specific elements of instructional design for surgical training multimedia-the user interface-have been conducted, see [8]. This has been characterized in the literature as an oversight that may mask the full educational benefits that multimedia could offer, where people adopt new learning methods without knowing their effectiveness, e.g., [9].…”
Section: Introductionmentioning
confidence: 76%